Profil TPACK Guru Ekonomi di Indonesia sebagai Pendekatan Integrasi TIK selama Pembelajaran Jarak Jauh pada Masa Pandemi Covid-19 - Villa Santika; Mientasih Indriayu; Khresna Bayu Sangka (Duconomics Sci-meet (Education & Economics Science Meet), 2021)
This study aims to determine the profile of teacher TPACK and its effect on teacher skills in integrating ICT in online learning during the Covid-19 pandemic. The population of this study were teachers of Economics in all regions of Indonesia, while the sample obtained was 271 respondents through convenience sampling technique and using a research instrument in the form of a questionnaire with a total of 20 items. The research method used is descriptive quantitative. The results showed that the average score of the seven components of TPACK was more than 80%, namely TK, PK, CK, TPK, TCK, PCK, and TPACK respectively 81.5%, 83.1%, 87.5%, 84 .0%, 86.3%, 85.3%, and 84.1%. Then, the integration of teacher ICT during online learning consisting of preparation of ICT-based learning, process of ICT-based learning, and evaluation of ICT-based learning has an average score of 87.3%, 84.7%, and 85.4%, indicating that the average score the ICT integration of teachers is more than 84%. So it can be said that a high TPACK can affect teacher skills in integrating ICT during online learning, especially during the current Covid-19 pandemic. For future research, it is possible to test the validity of this instrument and the relationship and influence of the TPACK variable factors on the integration of ICT teachers